2015
DOI: 10.1007/s00421-015-3132-x
|View full text |Cite
|
Sign up to set email alerts
|

Children have a reduced maximal voluntary activation level of the adductor pollicis muscle compared to adults

Abstract: The results suggest that on an untrained muscle such as the AP muscle, the reduced ability of children to voluntarily activate their muscle could partly account for the difference of muscle strength between children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The interplay of central vs. peripheral mechanisms of 321 fatigue in children remains to be elucidated; however, on the basis of these studies 322 Furthermore, when the initial MVC torque was used as covariate, no significant 406 difference in the course of the twitch torque was observed between groups, supporting 407 the importance of MVC torque in the development of fatigue. This finding is also 408 consistent with other studies that showed the fatigability of the knee extensors during 409 repeated MVC was no longer different between obese and non-obese adolescent girls Vicencio et al 2015). In addition, other studies reported that the greater fatigue 412 observed in men versus women was eliminated when subjects were matched for 413 absolute force (Hunter et al 2004).…”
Section: Resistance Exercise 245supporting
confidence: 86%
“…The interplay of central vs. peripheral mechanisms of 321 fatigue in children remains to be elucidated; however, on the basis of these studies 322 Furthermore, when the initial MVC torque was used as covariate, no significant 406 difference in the course of the twitch torque was observed between groups, supporting 407 the importance of MVC torque in the development of fatigue. This finding is also 408 consistent with other studies that showed the fatigability of the knee extensors during 409 repeated MVC was no longer different between obese and non-obese adolescent girls Vicencio et al 2015). In addition, other studies reported that the greater fatigue 412 observed in men versus women was eliminated when subjects were matched for 413 absolute force (Hunter et al 2004).…”
Section: Resistance Exercise 245supporting
confidence: 86%
“…Although some studies reported a comparable level of voluntary activation between children and adults [39] or between children and adolescents [40], other studies have reported a lower voluntary activation level in children compared to adolescents [41] and adults [33,42,43]. Overall, children have a reduced ability to maximally activate their MUs, which has often been attributed to a relative immaturity of the cortico-spinal pathway.…”
Section: Voluntary Activationmentioning
confidence: 99%
“…Sixty-seven percent (4/6) of these studies reported lower VA in children compared with adults ( 4 , 12 , 13 , 35 ). Of the studies investigating “older” children (>10 yr, n = 14), 35% (5/14) reported significantly lower VA in children compared with adults ( 10 , 11 , 14 , 33 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 67% (4/6) reported significantly lower VA in children compared with adults ( 4 , 10 , 12 , 33 ). Of the studies that applied the stimulus (electrical or magnetic) to the nerve, 36% (5/14) reported significantly lower VA in children than in adults ( 11 , 13 , 14 , 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%